DETERMINASI KEPUTUSAN REVALUTASI ASET TETAP (Studi Kasus Pada BUMN Listed di Bursa Efek Indonesia) - Marlina, Leli (Ekonomika Journal, 2022)
This research is a quantitative study which aims to determine the influence of fixed assets intensity, leverage, liquidity, cash flow from operations, and firm size on fixed asset revaluation decisions. The population used in this research is state-owned companies listed on the Indonesia Stock Exchange (BEI) in 2013-2017. The number of samples obtained using several criteria was 100 data. This research uses the logistic regression analysis method with the help of the E-Views (Statistical Product and Service Solution) data processing program version 10. The results of this research show that the fixed asset intensity variable has no effect on the decision to revaluate fixed assets, the liquidity variable and the cash flow from variable. operation has a significant negative effect on fixed asset revaluation decisions. Meanwhile, the leverage and firm size variables have a significant positive effect on fixed asset revaluation decisions